Effectiveness of Eco-Enzyme in Reducing pH, BOD, and NH₃ Levels in Wastewater from Jombang Regional General Hospital - Nahdya Ashiva Syam; Fitri Rokhmalia; Khambali Khambali; Suprijandani Suprijandani (Jurnal Ilmiah Kesehatan Masyarakat : Media Komunikasi Komunitas Kesehatan Masyarakat, 2026)
Background: Wastewater treatment at Jombang Regional General Hospital (RSUD Jombang) has not consistently met effluent quality standards for parameters such as pH, Biochemical Oxygen Demand (BOD), and ammonia (NH₃). In addition, environmentally friendly approaches, such as eco-enzymes, have not yet been optimally implemented. This study aimed to analyze the effectiveness of the eco-enzyme in reducing pH, BOD, and NH₃ levels in hospital wastewater at Jombang Regional General Hospital. Methods: This study employed a laboratory experimental design using a post-test-only control group approach. Phytochemical analysis was conducted to identify the bioactive compounds present in the eco-enzyme solution. Wastewater samples were collected from the Wastewater Treatment Plant (WWTP) of Jombang Regional General Hospital and treated with eco-enzyme concentrations of 5%, 10%, and 15% for an incubation period of 5 days. The measured parameters included pH, BOD, and ammonia (NH₃). Statistical analysis was performed using one-way analysis of variance (ANOVA) at a significance level of α = 0.05, followed by Tukey’s Honestly Significant Difference (HSD) post hoc test to determine differences among treatment groups. Results: Phytochemical analysis identified five main bioactive compounds in the eco-enzyme solustion, namely flavonoids (14.246 mg/mL), polyphenols (3.648 mg/mL), citric acid (0.6954 g/L), lactic acid (0.05 mg/mL), and bromelain (0.714 U/mL). Eco-enzyme treatment significantly reduced all measured wastewater parameters. The mean pH decreased from 8.18 to 6.00 (26.59%), BOD decreased from 73.63 mg/L to 38.57 mg/L (47.62%), and NH₃ decreased from 9.45 mg/L to 2.78 mg/L (70.52%) at the 15% eco-enzyme concentration. One-way ANOVA indicated statistically significant differences among eco-enzyme treatment groups for pH, BOD, and NH₃ parameters (p < 0.05), with the greatest reductions observed at the 15% eco-enzyme concentration. Conclusions: Eco-enzymes demonstrated potential effectiveness in reducing pH, BOD, and NH₃ levels in hospital wastewater, particularly at a concentration of 15%. These findings suggest that eco-enzymes may serve as a sustainable and cost-effective approach for hospital wastewater treatment. Further studies are required to optimize fermentation conditions, extend treatment duration, and evaluate large-scale applications to assess long-term stability and economic feasibility.